HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU MEROKOK PETUGAS KESEHATAN KAWASAN TANPA ROKOK (KTR) RUMAH SAKIT UMUM FANDIKA - Magfirah; Andi Pratama Putra; Muzaffar; Nurlaely HS (Jurnal Ilmiah Cerebral Medika, 2026)
ABSTRACT A Smoke-Free Area (KTR) is a room or area that is declared prohibited for smoking activities or activities of producing, selling, advertising, and/or promoting Tobacco Products. Regulation of the Minister of Health Number 4 of 2018 concerning Hospital Obligations and Patient Obligations states that every Hospital is required to enforce the entire hospital environment as a smoke-free area. This type of research is Quantitative with a Descriptive approach and cross-sectional design. With a population of 52 people, and a sample of 52 respondents. The sampling technique is total sampling. Data analysis uses the chi-square test. The results of the chi-square test correlation analysis obtained a significant value of knowledge of 0.0611> 0.05 and smoking behavior of 0.000 <0.05. So it can be concluded that there is no significant relationship between knowledge and smoking behavior of health workers in the smoke-free area (KTR) of Fandika General Hospital in 2024. It is recommended that the hospital form a special officer to implement the policy so that it runs well. Keywords : KTR, knowledge, smoking behavior